Defining institutions - A review and a synthesis - Claudius Gräbner; Amineh Ghorbani (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
Despite being a key term in institutional economics, the term 'institution' seems to be used in various different ways. To what extent is this problematic, given that a shared understanding of key terms among scholars is a necessary condition for scientific progress? We review prominent definitions of the term 'institution' and identify a set of shared elements of these definitions, which can be summarized as institutions being “codifiable systems of social structures (in particular norms and rules) that lead to inclinations for people to act in specific ways”. This suggests that the shared understanding of `institutions' is sufficiently concrete.
Keywords: B25; B4; B52; 330; Definitions; institutions; epistemology